STUDI KOROSI DAN SIFAT MEKANIS SAMBUNGAN LAS BUSUR RENDAM UNTUK KONSTRUKSI BAJA DENGAN PERLAKUAN PANAS - Wijayanto, Jarot; -, Darmansyah (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
The research in corrosion rate and mechanical properties for submerged arc welding of Steel construction through heat treatment, was done to study the effectiveness of the use of Post-Weld Heat Treatment (PWHT) using flame oxy aceteline. Its used for reducing the residual stress which may cause reduction in corrosion of resistance. Based on the study, it can be concluded that the release of residual stresses in submerged arc welding by PWHT can reduce current densities up to 43.88 Î¼A/cm2 at the specimen T300, and also reduce the rate of corrosion that sea water by concentration of 3.3% NaCl. The slowest of corrosion rate occurs in spesimen T300, i.e. 0.311 mm/year compared to the TT specimen that has corrosion rate of 0.377 mm/year. In general, the microstructure of a welding is ferrite of grain boundaries that form structure of the pillar (columnar) with acicular ferrite be inside the columnar grains. The specimens T300 reached optimum hardness value 222.240 VHN but get the lowest value of tensile strength i.e only 54.5 kg/mm2.